The Role of Fisheries Sector in Forming the Gross Regional Domestic Product of Southeast Sulawesi Province - Budiyanto Budiyanto; Irdam Riani; Ragil Larasati; Pini Ariska; Roslindah Daeng Siang; Ruslaini Ruslaini; Syamsul Kamri; Wa Ode Piliana (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
The fisheries sector, both capture fisheries, and aquaculture, needs to be developed in Southeast Sulawesi Province, considering that most of its territory is water. One of the indicators to measure the success of the development of the fisheries sector is the increase in production and added value of fishery commodities. On the other hand, Gross Regional Domestic Product (GRDP) can be used as an indicator of the success of economic development in a region. As one of the GRDP elements, the value of fisheries production can be used to measure the performance of the fisheries sector. By knowing the magnitude of the value contribution of fishery products to GRDP, it can be seen the role of the fisheries sector in the formation of GRDP. This study aims to analyze the trend of fishery production value contribution to GRDP; and the relationship between the value contribution of fishery production and GRDP in Southeast Sulawesi. The data used in this study is time series data consisting of capture and aquaculture production values ​​and GRDP for 17 years (2006-2022). Data analysis is descriptive quantitative and simple correlation analyses (Pearson correlation). The study results show that the value contribution of capture and aquaculture production to Southeast Sulawesi’s GRDP tends to decrease. The role of the fisheries sector in forming the GRDP of Southeast Sulawesi Province is not significant.